Can media drive the electorate? The impact of media coverage on party affiliation and voting intentions - Ralf Dewenter; Melissa Linder; Tobias Thomas (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2018)
As the rise of populist and right-wing political movements is connected to extensive media coverage, the question arises whether media report more on political parties because of their success or if their success is caused by media reports. To tackle this question, we investigate how media coverage affects short- and long-term political preferences, namely party affiliation and voting intention. For our empirical analysis, we merge 14 years of human-coded data obtained from leading media in Germany with results of the comprehensive German Politbarometer survey from February 1998 through December 2012. To account for endogeneity, we employ instrumental variable estimations. In addition, we control for a multitude of (internal) personal characteristics, such as age, and gender, as well as for (external) macroeconomic variables, such as business climate, unemployment, and inflation. The results show that media coverage of a political party has a positive and significant effect on the short-term voting intention for this party. When media outlets cover a political party more positively, the electorate has a greater tendency to vote for it. However, for long-term party affiliation, the effect vanishes. This is consistent with the economic theory. Long-term preferences are stable and, thus, contemporary events, such as media coverage, hardly affect supposedly stable preferences. However, in the long-term, party affiliation might also be affected.
Keywords: C43; D72; 330; political preferences; voting intention; media impact